2022
DOI: 10.1016/j.mmcr.2021.12.002
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-associated brain abscess caused by Trichosporon dohaense: A case report and review of literature

Abstract: We report the first case of Coronavirus Disease 2019 (COVID-19)-associated brain abscess caused by a rare Trichosporon species, T. dohaense . The patient was a known diabetic and had received systemic corticosteroids for the treatment of COVID-19. He underwent craniotomy and evacuation of abscess. The pus aspirate grew a basidiomycetous yeast, morphologically resembling Trichosporon species. The isolate was initially misidentified by VITEK® M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The mortality rate was 77.7% [90]. T. dohaense caused brain abscess associated with COVID-19, a rare infection not previously described, in the central nervous system of a diabetic patient aged 55 years [93].…”
Section: Trichosporon Sppmentioning
confidence: 81%
See 1 more Smart Citation
“…The mortality rate was 77.7% [90]. T. dohaense caused brain abscess associated with COVID-19, a rare infection not previously described, in the central nervous system of a diabetic patient aged 55 years [93].…”
Section: Trichosporon Sppmentioning
confidence: 81%
“…show high MICs for AmB (1µg/mL), T. dohaense consistently demonstrated low MICs. Among the more recent triazoles, voriconazole (0.125 1µg/mL) and posaconazole (0.25 1µg/mL) exhibit potent in vitro activity against T. dohaense [93,94]. Invasive trichosporonosis carries a high mortality rate (40-60%) despite antifungal therapy [95].…”
Section: Trichosporon Sppmentioning
confidence: 99%
“…A few studies have reported invasive cerebral infections with unusual organisms in patients with COVID-19 (Table 1 ). Two studies reported fungal brain abscesses associated with trichosporonosis and phaeohyphomycosis, both in patients with diabetes[ 22 , 23 ]. This suggests that COVID-19 infection can predispose patients to unusual infections with unusual pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 ] 2022 Female 73 Hypertension, DM Fonsecaea Death Samaddar et al. [ 23 ] 2022 Male 55 Hypertension, DM Trichosporon dohaense Recovery Gupta et al. [ 32 ] 2021 Male 62 DM Aspergillus fumigatus Recovery De Villiers De La Noue et al.…”
Section: Discussionmentioning
confidence: 99%
“…Almeida-Jr. [51], described 5 critical patients with COVID-19 who developed fungemia by T. asahii, who presented risk conditions: central venous catheter, previous exposure to broad-spectrum antibiotics, previous therapy with echinocandin and previous prolonged corticosteroid therapy. More currently, Cronyn [52] reported urinary infection in a male patient with severe COVID-19, isolating the co-infection agent T. asahii, treated with fluconazole and voriconazole, and finally, a case of associated brain abscess to Coronavirus Disease 2019 caused by a rare species of basidiomycete of the genus Trichosporon, T. dohaense affecting a diabetic patient who received systemic corticosteroids for the treatment of COVID-19 [53].…”
Section: Reports Of Immunosuppression In Cases Of Sars-covmentioning
confidence: 99%